2006
DOI: 10.1002/ps.1291
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct gene expression patterns induced by the herbicides 2,4‐dichlorophenoxyacetic acid, cinidon‐ethyl and tribenuron‐methyl in wheat

Abstract: In wheat, herbicides are used to control weeds. Little is known about the changes induced in the metabolism of tolerant plants after herbicide treatment. The impact of three herbicides [2,4-dichlorophenoxyacetic acid (2,4-D), cinidon-ethyl and tribenuron-methyl] on the wheat transcriptome was studied using cDNA microarrays. Gene expression of plants grown in a controlled environment or in the field was studied between 24 h and 2 weeks after treatment. Under controlled conditions, 2,4-D induced genes of the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…Otherwise, expression of certain genes would be affected by biotic and abiotic stresses, and other environmental factors. Lower expression in naturally infected, compared to experimentally infected, plants support the result of other related research that showed the same genes in herbicide treated wheat, as under controlled conditions, were up-regulated in the field at a weaker level [59]. …”
Section: Resultssupporting
confidence: 76%
“…Otherwise, expression of certain genes would be affected by biotic and abiotic stresses, and other environmental factors. Lower expression in naturally infected, compared to experimentally infected, plants support the result of other related research that showed the same genes in herbicide treated wheat, as under controlled conditions, were up-regulated in the field at a weaker level [59]. …”
Section: Resultssupporting
confidence: 76%
“…However, indirect tolerance by the effective scavenging of the byproducts of oxidative stress caused by the inhibitory activity of the herbicides is also important, as demonstrated by the increased tolerance to oxyfluorfen, which is not detoxified by glutathione conjugation. As shown by microarray analysis in wheat treated with cinidon-ethyl, a herbicide that also inhibits protoporphyrinogen oxidase, the primary response of wheat was the upregulation of genes coding for antioxidant enzymes, thus indicating the importance of counteracting oxidative stress caused by these peroxidizing herbicides (Pasquer et al, 2006). The dual GST/GPOX function of many GSTs might contribute to peroxidizing herbicides tolerance in soybean (Skipsey et al, 1997) and in weed species , and is of great importance in alleviating abiotic stresses mediated oxidative stress (Kilili et al, 2004;Roxas et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, temporal patterns of gene expression (as reported with different herbicides by Pasquer et al, 2006) in response to safeners or RES oxylipins would be extremely informative from the standpoint of understanding the time course of plant responses to a potent inducer of xenobiotic detoxification, in comparison with endogenous RES oxylipin signaling molecules. From a molecular standpoint, it would be of great interest to determine if regulation of OPR gene expression in response to various stresses occurs at the transcriptional, posttranscriptional, or posttranslational level.…”
Section: Future Research Areas To Explorementioning
confidence: 99%